Synthesis and Application of PHT‐TiO2 Nanohybrid for Amperometric Glucose Detection in Human Saliva Sample. Issue 11 (27th September 2018) - Kadian, Sachin; Arya, Brahm Dutt; Kumar, Sumit; Sharma, Shailesh N.; Chauhan, Rishi Pal; Srivastava, Ananya; Chandra, Pranjal; Singh, Surinder P.
Abstract: Nanoparticles and their composites are considered to play a significant role in the development of electrochemical biosensors. In the present work, we have synthesized titanium dioxide (TiO2 ) nanoparticles comprising poly (3‐hexylthiophene) (PHT) nanohybrid for the fabrication of glucose biosensor. The thin film of hybrid PHT/TiO2 nano‐composite was deposited onto indium‐tin‐oxide (ITO) glass substrate followed by immobilization of glucose oxidase (GOx). The developed sensor was characterized using X‐Ray Diffraction, Fourier Transform Infrared Spectroscopy, UV‐visible spectroscopy, cyclic voltammetry, electrochemical impedance spectroscopy, and scanning electron microscopy. The electrochemical response of the nanocomposite coated electrode was studied which shows a quasi‐reversible electrochemical behavior. The experimental conditions for glucose detection were optimized in terms of GOx immobilization time, GOx concentrations, temperature, and pH, in order to obtain maximum sensitivity. Under the optimized experimental conditions, the ITO/TiO2 /PHT/GOx sensor probe displays excellent catalytic activity towards glucose with the response time of <10.0 sec, showing its robustness for direct clinical analysis. Chronoamperometry was performed for the quantitative detection of glucose which displays the linear dynamic range between 1–310 mg/dL with the detection limit of 0.62±0.02 mg/dL. The developed biosensor was successfully applied to detect glucose in human saliva samples without any pre‐treatment step. Importantly, the detection range of the designed biosensor was in range of normal and clinical salivary glucose levels. Interferences due to nontarget biochemicals was investigated and long term stability of the sensor probe was evaluated. Abstract :